Understanding the Factors That Influence Debt Burden in College Graduates (International Journal of Innovative Research in Engineering & Management, 2021)
This study looks at debt burden among  college graduates and compares it to previous research by  taking institutional and state variables into consideration.  Using a combination of national datasets using zero-one  inflated beta regression, we uncover a number of interesting  trends. First, family income and college experiences have a  substantial impact on the chance of having no debt and the  degree of debt burden. Second, graduates of private colleges  are more likely than graduates of public universities to be in  debt. Finally, although state funding of merit-based aid  programs helps to lower student debt, when the "Georgia  effect" is taken into account, the advantage is lost. On the  roles that institutions and the government may play in  reducing student debt, conclusions and suggestions are  provided. Grants currently account for just 52 percent of total  undergraduate financial aid, with the remaining 39 percent  coming from government and commercial loans. As a result  of these changes in federal and state regulations, there has  been a large increase in student borrowing. Between 1995– 96 and 2007–08, the percentage of undergraduates  borrowing increased from 37.8% to 46.2 percent at public  four-year colleges and from 48.5 percent to 58.9% at private,  nonprofit four-year schools.
Keywords: College Graduate; Debt Burden; Education; Financing Education